(untitled) (Eurasian Journal of Ecology, 2016)
This paper considers one of modern tracks of biotechnology, and namely the development of production technology for biologically active substances. Screening of common bean cultivars and specimens has been performed to show that some of Kazakhstani patterns would be characterized by higher content of total soluble protein and lectins. Study on callus formation properties for these common bean cultivars has allowed to determine optimal conditions for the propagation of cell biomass that would be used for the accumulation of lectins and working out biotechnology methods for their isolation.